2015
DOI: 10.5045/br.2015.50.3.154
|View full text |Cite
|
Sign up to set email alerts
|

MDR1/ABCB1gene polymorphisms in patients with chronic myeloid leukemia

Abstract: BackgroundTyrosine kinase inhibitors (TKIs) are the recommended treatment for patients with chronic myeloid leukemia (CML). The MDR1/ABCB1 gene plays a role in resistance to a wide spectrum of drugs, including TKIs. However, the association of MDR1/ABCB1 gene polymorphisms (SNPs) such as C1236T, G2677T/A, and C3435T with the clinical therapeutic evolution of CML has been poorly studied. We investigated these gene polymorphisms in CML-patients treated with imatinib, nilotinib and/or dasatinib.MethodsABCB1-SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…Since previous studies showed that TKIs including imatinib, nilotinib and dasatinib were substrates of MDR-1, the therapeutic effects of TKIs are greatly affected by MDR-1 expression. [13][14][15][16][17] Indeed, our study showed that dasatinib completely suppressed proliferation of parent K562 cells after short-term exposure at a final concentration of 100 ng/mL, but did not suppress proliferation of hMDR-1-transfected cells (Fig. 4D).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Since previous studies showed that TKIs including imatinib, nilotinib and dasatinib were substrates of MDR-1, the therapeutic effects of TKIs are greatly affected by MDR-1 expression. [13][14][15][16][17] Indeed, our study showed that dasatinib completely suppressed proliferation of parent K562 cells after short-term exposure at a final concentration of 100 ng/mL, but did not suppress proliferation of hMDR-1-transfected cells (Fig. 4D).…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have also shown a relationship between therapeutic effect and MDR-1 overexpressions. [13][14][15][16][17] Therefore, it is also necessary to consider the possibility that MDR-1, which is responsible for tolerance of treatment with TKIs, affects maintenance of the therapeutic effect by administration every other day.…”
Section: Introductionmentioning
confidence: 99%
“…A haplotype analysis within ABCB1 performed, i.a., in neoplastic and neurological diseases turned out to be a useful tool in terms of evaluation of the morbidity and the effectiveness of treatment [2, 4, 20, 22, 23, 27, 42, 43, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…Отсутствие влияния отдельного полиморфизма C3435T (rs1045642) гена MDR1 на риск развития хронических миелопролиферативных заболеваний или развития резистентности к иматинибу в целом согласуется с опубликованными ранее данными о важности одновременной оценки носительства комплекса наиболее информативных однонуклеотидных замен как в гене MDR1, так и в других генах, определяющих распределение и метаболизм ксенобиотиков [3][4][5][6][7][8][9], а также репарацию повреждений ДНК [3].…”
Section: Discussionunclassified
“…Показано также, что слабый полиморфизм C3435T гена MDR1 ассоциирован с более высоким риском развития онкогематологических заболеваний: острых лейкозов [2] и ХМЛ [3,4]. В различных этнических группах было продемонстрировано влияние полиморфизмов MDR1 на развитие резистентности к терапии ХМЛ иматинибом [3][4][5][6][7][8][9]. Было также предложено первичное использование второй линии препаратов, устойчивых к Pgp-эффлюксу, вместо иматиниба у пациентов с полиморфизмами высокого риска резистентности [9].…”
Section: A Study Of the Association Of C3435t Polymorphism Of Mdr1 Geunclassified